Bio-based degradable high-temperature-resistant benzoxazine resin and preparation method thereof
By introducing a biacetal structure and hydroxymethyl into benzoxazine resin, the problem of poor heat resistance of existing benzoxazine resins is solved, achieving high heat resistance and biodegradability, making it suitable for recycling and reuse of fiber-reinforced composite materials.
Patent Information
- Application Number
- CN202411605689.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-12
AI Technical Summary
Existing benzoxazine resins are difficult to degrade and recycle while maintaining high heat resistance.
A biodegradable rigid biacetal structure and hydroxymethyl group were introduced into benzoxazine resin to improve its heat resistance through a crosslinking reaction, and the resin was prepared using bio-based raw materials.
It achieves high heat resistance and biodegradability under acidic conditions, is suitable for recycling and reuse of fiber-reinforced composite materials, and has an environmentally friendly preparation process.
Smart Images

Figure CN119285883A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermosetting resins, in particular to a bio-based degradable high-temperature resistant benzoxazine resin and a preparation method thereof. Background Art
[0002] Due to the dense three-dimensional cross-linked network in its molecular structure, thermosetting resins usually have high heat resistance, rigidity, dimensional stability, etc. Therefore, they are widely used in fiber-reinforced composites, coatings, adhesives, electronic packaging materials, circuit boards, aerospace materials and other fields, promoting social production progress. However, the three-dimensional cross-linked structure is also a "double-edged sword", making it difficult to recycle thermosetting resins and their fiber-reinforced composites after exceeding their service life, which puts a burden on the ecological environment. Benzoxazine is a class of six-membered heterocyclic compounds generated by phenol, amine and aldehyde through the Mannich reaction. It can undergo ring-opening polymerization under heating or catalyst to generate a nitrogen-containing and phenolic resin-like network structure. Compared with traditional phenolic resins, this new type of thermosetting resin has many unique properties, such as better molecular design, no small molecule release during curing, near-zero volume shrinkage, high strength and high modulus, high residual carbon rate, high temperature resistance, etc. Like most other thermosetting resins, benzoxazine resins are also difficult to degrade and recycle after curing.
[0003] For the existing chemical recycling methods, the main method is to introduce some unstable or dynamically exchangeable bonds under certain conditions into the synthetic monomers to achieve the degradability of thermosetting resins, which is currently a relatively feasible method. This type of resin can be efficiently degraded under certain conditions to achieve the purpose of recycling raw materials, reducing environmental pollution and production costs. However, their performance will deteriorate due to the introduction of unstable reversible structures, and the most obvious one is the heat resistance. There are few reports that degradable thermosetting resins are heat-resistant above 260°C. For example, patent CN110551140A discloses a benzoxazine resin containing a spirocyclic acetal structure and a preparation method thereof. A benzoxazine resin containing a spirocyclic acetal structure is prepared by a solution synthesis method from a bisphenol compound containing a spirocyclic acetal structure and a primary amine compound and an aldehyde compound. The prepared benzoxazine resin has a good chemical degradation property after curing, and the recovery and reuse of waste materials are realized; however, the heat resistance of the benzoxazine resin needs to be improved.
[0004] Therefore, there is an urgent need to develop a new benzoxazine resin material that can make the benzoxazine resin biodegradable, recyclable and reusable while maintaining its original high heat resistance. Summary of the invention
[0005] In view of the problem that the current degradable benzoxazine resin has poor heat resistance, the present invention provides a bio-based degradable high temperature resistant benzoxazine resin and a preparation method thereof.
[0006] The present invention introduces a degradable rigid diacetal structure and a hydroxymethyl group into the benzoxazine resin. The diacetal structure enables it to achieve degradable recycling while still retaining good heat resistance. In addition, the hydroxymethyl group can also undergo a cross-linking reaction to further improve the heat resistance, and finally a highly heat-resistant benzoxazine resin with degradable characteristics is obtained.
[0007] The bio-based degradable high temperature resistant benzoxazine resin of the present invention is obtained by curing the benzoxazine monomer having the molecular structure shown in formula (I) by heating:
[0008]
[0009] Wherein, A1 and A2 are each independently selected from one of formula (II) to formula (IV); A1 and A2 may be the same or different.
[0010]
[0011] Wherein, R1, R2, and R3 are each independently selected from any one of an aliphatic group, an alicyclic group, or an aromatic group.
[0012] The aliphatic group is one of methyl, ethyl or n-hexyl.
[0013] The alicyclic group is 2-furylmethyl or cyclohexyl.
[0014] The aromatic group is one of phenyl, p-tolyl, m-tolyl or m-phenylethynyl.
[0015] The present invention also provides a method for preparing a bio-based degradable high temperature resistant benzoxazine resin, comprising the following steps:
[0016] S1. Add the primary amine compound and the aldehyde compound A into an organic solvent, and stir the mixture at a temperature of 90 to 120° C. for 10 to 60 minutes to generate a triazine compound.
[0017] The primary amine compound is selected from any one of methylamine, ethylamine, n-hexylamine, 2-furylamine, cyclohexylamine, aniline, p-toluidine, m-toluidine or m-aminophenylacetylene.
[0018] The organic solvent is selected from one or more of ethanol, tetrahydrofuran, acetone, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, dioxane, chloroform, toluene or xylene.
[0019] S2. Add the bisphenol compound containing a hydroxymethyl diacetal structure and the aldehyde compound B to the solution obtained in step S1, and stir the reaction at 60-90° C. for 1-15 hours.
[0020] The bisphenol compound containing a hydroxymethyl diacetal structure is xylitol di-p-hydroxybenzaldehyde or xylitol di-m-hydroxybenzaldehyde; the preparation method is as follows:
[0021] Take xylitol, p-hydroxybenzaldehyde or m-hydroxybenzaldehyde as reactants, p-toluenesulfonic acid as a catalyst, N,N-dimethylformamide and petroleum ether as solvents, mix them evenly at room temperature, then heat to 80-140° C., stir and react for 8-24 hours, and remove the solvent by rotary evaporation to obtain sugar alcohol bis-p-hydroxybenzaldehyde or xylitol bis-m-hydroxybenzaldehyde.
[0022] The mass ratio of xylitol, p-hydroxybenzaldehyde or m-hydroxybenzaldehyde, p-toluenesulfonic acid, N,N-dimethylformamide and petroleum ether is 1: (1.1-2.2): (0.05-0.15): (3.60-4.80): (2.40-3.60).
[0023] The organic solvent is selected from one or more of ethanol, tetrahydrofuran, acetone, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, dioxane, chloroform, toluene or xylene.
[0024] The aldehyde compounds A and B may be the same or different, and are both selected from 37% formaldehyde aqueous solution or paraformaldehyde.
[0025] S3. After the reaction is completed, the reaction product is first washed with a 1 mol / L sodium hydroxide aqueous solution, the solid is collected by filtration, the solid is washed with deionized water until neutral, and vacuum dried to obtain a benzoxazine monomer.
[0026] S4. Curing the obtained benzoxazine monomer by increasing the temperature. The curing process is as follows: degassing at 120° C. for 1 hour, and then curing at 140 to 220° C. for 4 to 8 hours to obtain a benzoxazine resin.
[0027] Preferably, in step S1, the molar ratio of the amino group of the primary amine compound to the aldehyde group of the aldehyde compound A is 1:(1.0-1.3).
[0028] Preferably, in step S2, the molar ratio of triazine, phenolic hydroxyl group and aldehyde group in the three reaction raw materials is 1:(1.3-1.7):(3.0-3.5).
[0029] The benzoxazine monomer prepared in step S2 of the present invention may be any one of the structures shown in the following (1) to (11).
[0030] (1) Xylitol di-p-hydroxybenzaldehyde / aniline type
[0031]
[0032] (2) Xylitol di-p-hydroxybenzaldehyde / methylamine type
[0033]
[0034] (3) Xylitol di-p-hydroxybenzaldehyde / ethylamine type
[0035]
[0036] (4) Xylitol bis(4-hydroxybenzaldehyde) / 2-furanylamine type
[0037]
[0038] (5) Xylitol di-p-hydroxybenzaldehyde / cyclohexylamine type
[0039]
[0040] (6) Xylitol di-p-hydroxybenzaldehyde / p-methylaniline type
[0041]
[0042] (7) Xylitol di-p-hydroxybenzaldehyde / m-aminophenylacetylene type
[0043]
[0044] (8) Xylitol di-m-hydroxybenzaldehyde / aniline type
[0045]
[0046] (9) Xylitol di-m-hydroxybenzaldehyde / methylamine type
[0047]
[0048] (10) Xylitol di-m-hydroxybenzaldehyde / ethylamine type
[0049]
[0050] (11) Xylitol bis(m-hydroxybenzaldehyde) / 2-furanylamine type
[0051]
[0052] The present invention also provides a method for degrading a benzoxazine resin, comprising soaking the benzoxazine resin in a mixed solution for 1 to 48 hours; the mixed solution comprises an acid compound and a polar solvent.
[0053] The acid compound is one or more of organic acids such as formic acid, acetic acid, oxalic acid, citric acid, etc., or one or more of inorganic acids such as hydrochloric acid, sulfuric acid or phosphoric acid.
[0054] The polar solvent is one or more of an alcohol compound, a ketone compound, an ether compound or an amide compound. The alcohol compound is one or more of methanol, ethanol and glycerol. The ketone compound is acetone or butanone. The ether compound is tetrahydrofuran or 1,4-dioxane. The amide compound is one or more of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.
[0055] Compared with the prior art, the present invention is beneficial in that:
[0056] (1) The benzoxazine resin of the present invention introduces a hydroxymethyl diacetal structure, and the hydroxymethyl group can undergo a cross-linking reaction to increase the cross-linking density of the cured product, thereby further improving the heat resistance of the cured product; the benzoxazine resin has excellent heat resistance, and the glass transition temperature of the cured product can reach up to 305°C.
[0057] (2) The cured product of the benzoxazine resin containing a hydroxymethyl diacetal structure of the present invention has good chemical degradation properties after being cured and can be degraded under acidic conditions, thereby further realizing the recycling and reuse of fiber-reinforced composite products.
[0058] (3) The diphenol containing a hydroxymethyl diacetal structure of the present invention is prepared from all-biobased raw materials. The preparation process of the benzoxazine resin is simple, the conditions are mild, it is environmentally friendly, it is easy to operate, and it has strong practicality. It can be applied to the fields of laminated boards.
[0059] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the benzoxazine monomer obtained in Example 1.
[0061] Figure 2 This is the Fourier transform infrared spectrum of the benzoxazine monomer obtained in Example 1.
[0062] Figure 3 This is the DSC spectrum of the benzoxazine monomer obtained in Example 1.
[0063] Figure 4 This is the TGA spectrum of the benzoxazine monomer cured material obtained in Example 1.
[0064] Figure 5This is the DMA spectrum of the benzoxazine monomer cured material obtained in Example 1.
[0065] Figure 6 This is the hydrogen nuclear magnetic resonance spectrum of the benzoxazine monomer obtained in Example 4.
[0066] Figure 7 This is the Fourier infrared spectrum of the benzoxazine monomer obtained in Example 4.
[0067] Figure 8 This is the DSC spectrum of the benzoxazine monomer obtained in Example 4.
[0068] Fig. 9 This is the TGA spectrum of the benzoxazine monomer cured material obtained in Example 4.
[0069] Fig.10 This is the DMA spectrum of the benzoxazine monomer cured material obtained in Example 4. DETAILED DESCRIPTION
[0070] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0071] The xylitol di-p-hydroxybenzaldehyde used in the following Examples 1-7 is prepared as follows:
[0072] Weigh 1g of xylitol, 2g of p-hydroxybenzaldehyde, 0.1g of p-toluenesulfonic acid, 4.0g of N,N-dimethylformamide, and 3.0g of petroleum ether, mix these raw materials evenly at room temperature, then heat to 120°C, stir and react for 15 hours, and after the reaction, remove the solvents N,N-dimethylformamide and petroleum ether by rotary evaporation to obtain xylitol di-p-hydroxybenzaldehyde.
[0073] If it is necessary to prepare xylitol bis-m-hydroxybenzaldehyde acetal, the same method as above can be used, except that p-hydroxybenzaldehyde needs to be replaced by m-hydroxybenzaldehyde.
[0074] Example 1
[0075] A method for preparing a bio-based degradable high temperature resistant benzoxazine resin:
[0076] Step 1: weigh the raw materials according to the molar ratio of amine group: aldehyde group = 1: 1.2, add 9.31g (0.1mol) of aniline, 3.6g (0.12mol) of paraformaldehyde and 100mL of DMF in a 250mL three-necked flask, stir and mix at 100°C for 20min until the reaction is complete, and obtain the intermediate product triazine;
[0077] Step 2: According to the molar ratio of triazine, phenolic hydroxyl group and aldehyde group of 1:1.4:3.3, 50.46 g (0.14 mol) of xylitol di-p-hydroxybenzaldehyde and 9.9 g (0.33 mol) of polyformaldehyde were added to the three-necked flask in step 1, and the temperature was gradually raised to 90°C, and the reaction was carried out at a constant temperature for 7 hours.
[0078] Step 3: After the reaction is completed, the reaction product is first washed with a 1 mol / L sodium hydroxide aqueous solution, filtered, and the solid product is then washed with deionized water until neutral. The product is vacuum dried at 60° C. to obtain a benzoxazine monomer, which is a xylitol di-p-hydroxybenzaldehyde / aniline type benzoxazine monomer, and the yield calculated by weighing is 92.3%.
[0079] Step 4: Curing the obtained benzoxazine monomer by heating, the process is as follows: degassing at 120° C. for 1 h, keeping at 140° C., 160° C., 180° C., and 200° C. for 2 h respectively, and then naturally cooling to room temperature to obtain benzoxazine resin.
[0080] The final product was tested and characterized by NMR, IR, DSC and TGA. The obtained NMR hydrogen spectrum, IR spectrum, DSC curve, TGA curve and DMA curve are shown as follows: Figure 1 , Figure 2 , Figure 3 , Figure 4 and Figure 5 shown.
[0081] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the benzoxazine monomer prepared in step 3. The chemical shifts of 5.35 ppm and 4.63 ppm are the characteristic peaks of the methylene group on the oxazine ring.
[0082] Figure 2 This is the infrared spectrum of the benzoxazine monomer prepared in step 3, where 938 cm -1 The absorption peak at is the characteristic absorption peak of benzoxazine ring.
[0083] Figure 3 FIG. 5 is a DSC curve of the benzoxazine monomer prepared in step 3. The peak temperature of the curing exothermic reaction of the benzoxazine monomer is 225° C.
[0084] Figure 4 This is the TGA spectrum of the material after curing the benzoxazine monomer. It can be seen that the temperature at which the polybenzoxazine resin loses 5% of its thermal weight is 297°C, and the carbon residue rate at 800°C is 50%.
[0085] Figure 5DMA spectrum of the material after curing of benzoxazine monomer, it can be seen that its glass transition temperature is 305° C. This is because the benzoxazine resin of the present invention introduces a hydroxymethyl diacetal structure, and the hydroxymethyl group can undergo a cross-linking reaction to increase the cross-linking density of the cured product, thereby improving the heat resistance of the cured product.
[0086] Example 2
[0087] The preparation process of Example 1 was repeated, except that the solvent used in step 1 was toluene, the amount of xylitol bis(p-hydroxybenzaldehyde) added in step 2 was 46.88 g (0.13 mol), and the amount of paraformaldehyde added was 10.5 g (0.35 mol), that is, the molar ratio of triazine, phenolic hydroxyl group, and aldehyde group was 1:1.3:3.5 (molar ratio), and the yield was 90.1%. The obtained product was subjected to NMR, IR characterization, DSC and other tests, and the results were almost consistent with those of Example 1.
[0088] Example 3
[0089] The preparation process of Example 1 was repeated, except that the solvent used in step 1 was dimethyl sulfoxide, the amount of xylitol bis-p-hydroxybenzaldehyde added in step 2 was 57.67 g (0.16 mol), and the amount of paraformaldehyde added was 9.3 g (0.31 mol), that is, the molar ratio of triazine, phenolic hydroxyl group, and aldehyde group was 1:1.6:3.1 (molar ratio), the constant temperature reaction time was 6 h, and the yield was 85.3%. The obtained product was subjected to NMR, IR characterization, DSC and other tests, and the results were almost consistent with those of Example 1.
[0090] Example 4
[0091] A method for preparing a bio-based degradable high temperature resistant benzoxazine resin:
[0092] Step 1: weigh the raw materials according to the molar ratio of amine group: aldehyde group = 1:1.1, add 9.7g (0.1mol) of 2-furanmethylamine, 3.3g (0.11mol) of paraformaldehyde and 100mL of dioxane in a 250mL three-necked flask, stir and mix at 120°C for 10min until the reaction is complete, and obtain the intermediate product triazine;
[0093] Step 2: According to the molar ratio of triazine, phenolic hydroxyl group and aldehyde group of 1:1.5:3.2, 54.07 g (0.0.15 mol) of xylitol di-p-hydroxybenzaldehyde and 9.6 g (0.32 mol) of polyformaldehyde were added to the three-necked flask in step 1, and the temperature was gradually raised to 90°C, and the reaction was carried out at a constant temperature for 7 hours.
[0094] Step 3: After the reaction is completed, the reaction product is first washed with a 1 mol / L sodium hydroxide aqueous solution, filtered, and the solid product is washed with deionized water until neutral. The product is vacuum dried at 60° C. to obtain a benzoxazine monomer, which is a xylitol bis(4-hydroxybenzaldehyde) / 2-furanylamine type benzoxazine monomer, and the yield calculated by weighing is 94.1%.
[0095] Step 4: Curing the obtained benzoxazine monomer by heating, the process is as follows: degassing at 120°C for 1 hour, keeping warm at 140°C, 160°C, 180°C, and 200°C for 2 hours respectively, and then naturally cooling to room temperature to obtain a cured product, namely, benzoxazine resin.
[0096] Figure 6 This is the hydrogen nuclear magnetic resonance spectrum of the benzoxazine monomer. The chemical shifts of 4.84 ppm and 3.96 ppm are the characteristic peaks of the methylene group on the oxazine ring.
[0097] Figure 7 This is the infrared spectrum of benzoxazine monomer, where 927cm -1 The absorption peak at is the characteristic absorption peak of benzoxazine ring.
[0098] Figure 8 FIG. 5 is a DSC curve of a benzoxazine monomer. The peak temperature of the curing exothermic reaction of the benzoxazine monomer is 233° C.
[0099] Fig. 9 This is the TGA spectrum of the material after curing the benzoxazine monomer. It can be seen that the temperature at which the polybenzoxazine resin loses 5% of its thermal weight is 278°C, and the carbon residue rate at 800°C is 51%.
[0100] Fig.10 This is the DMA spectrum of the material after curing of benzoxazine monomer. It can be seen that its glass transition temperature is 276°C.
[0101] Example 5
[0102] Step 1: Weigh the raw materials according to the ratio of amine group to aldehyde group = 1:1 (molar ratio), add 9.7 g (0.1 mol) of 2-furanmethylamine, 3 g (0.1 mol) of polyformaldehyde and 100 mL of xylene in a 250 mL three-necked flask, stir and mix at 90° C. for 60 min until the reaction is complete, and obtain the intermediate product triazine;
[0103] Step 2: Weigh according to the molar ratio of triazine, phenolic hydroxyl and aldehyde groups of 1:1.7:3.5, add 61.27 g (0.17 mol) of xylitol di-p-hydroxybenzaldehyde and 10.5 g (0.35 mol) of polyformaldehyde into the three-necked flask of step 1, gradually raise the temperature to 90°C, and react at a constant temperature for 7 hours.
[0104] Step 3: After the reaction is completed, the reaction product is first washed with a 1 mol / L sodium hydroxide aqueous solution, and then washed with deionized water until neutral. The product is vacuum dried at 60°C to obtain the final product. The yield calculated by weighing is 40.6%.
[0105] Step 4: Curing the obtained benzoxazine monomer by heating, the process is as follows: degassing at 120°C for 1 hour, keeping warm at 140°C, 160°C, 180°C, and 200°C for 2 hours respectively, and then naturally cooling to room temperature to obtain a cured product, namely, benzoxazine resin.
[0106] Example 6
[0107] The preparation process of Example 5 was repeated, except that 10.72 g (0.0.10 mol) of p-toluidine was used in step 1 instead of 9.7 g (0.0.10 mol) of 2-furanmethylamine, and dioxane was used as the solvent; the phenol used in step 2 was xylitol di-m-hydroxybenzaldehyde acetal, and the calculated yield was 74.9%.
[0108] Example 7
[0109] The preparation process of Example 5 was repeated, except that 11.72 g (0.10 mol) of m-aminophenylacetylene was used instead of 9.7 g (0.10 mol) of 2-furanmethylamine in step 1; and the phenol used in step 2 was xylitol bis-m-hydroxybenzaldehyde acetal. The calculated yield was 72.1%.
[0110] Comparative Example 1
[0111] Step 1: weigh the raw materials according to the molar ratio of amine group: aldehyde group = 1: 1.1, add 9.31g (0.0.10mol) of aniline, 3.3g (0.11mol) of polyformaldehyde and 100mL of toluene in a 250mL three-necked flask, stir and mix at 100°C for 20min until the reaction is complete, and obtain the intermediate product triazine;
[0112] Step 2: Weigh the triazine, phenolic hydroxyl and aldehyde groups in a molar ratio of 1:1.6:3.1, add 36.52 g (0.16 mol) of bisphenol A and 9.3 g (0.31 mol) of polyformaldehyde into the three-necked flask of step 1, gradually raise the temperature to 90°C, and react at a constant temperature for 7 hours.
[0113] Step 3: After the reaction is completed, the reaction product is first washed with a 1 mol / L sodium hydroxide aqueous solution, and the solid product is collected by filtration. The solid product is washed with deionized water until it is neutral, and the product is vacuum dried at 60°C to obtain the final product. The yield calculated by weighing is 80.2%.
[0114] Step 4: Curing the obtained benzoxazine monomer by heating, the process is as follows: degassing at 120°C for 1 hour, keeping warm at 140°C, 160°C, 180°C, and 200°C for 2 hours respectively, and then naturally cooling to room temperature to obtain a cured product, namely, benzoxazine resin.
[0115] Degradability test of benzoxazine:
[0116] The cured product of Comparative Example 1 and the cured product of Example 1 were placed in different mixed solutions, heated to different temperatures (30° C. or 80° C.) and degraded for a certain period of time, filtered, dried to constant weight, and weighed to calculate the degradation rate. The degradation rate calculation formula is as follows:
[0117]
[0118] After different degradation times, the degradation rate results are shown in Table 1.
[0119] Table 1. Degradation of the cured products of Comparative Example 1 and Example 1 in the mixed solution
[0120]
[0121]
[0122] From the data in Table 1, it can be seen that the cured products of Comparative Example 1 and Example 1 are placed in a solution with a volume ratio of DMSO: hydrochloric acid (1M) of 10:1, and after degradation for 12 hours at the same temperature (80°C), the degradation rate of the cured product of Comparative Example 1 is 0.6%, that is, almost no degradation occurs, and the degradation rate of the cured product of Example 1 is 72.7%. It shows that the presence of the diacetal structure makes the polybenzoxazine resin degradable under acidic conditions. It can also be seen from Table 1 that the cured product of Example 1 has different degrees of degradation in different mixed solutions. Under the same other conditions, the higher the degradation temperature, the higher the degradation speed and degradation rate. In addition, under the same solution and temperature, the longer the degradation time and the stronger the acidity, the higher the degradation rate.
[0123] The above results show that the polybenzoxazine resin containing a hydroxymethyl diacetal structure prepared by the present invention not only has good chemical degradation properties and can be degraded under acidic conditions, thereby realizing the recycling and reuse of fiber-reinforced composite products; it also has significant high temperature resistance.
[0124] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A bio-based degradable high temperature resistant benzoxazine resin, characterized in that: The benzoxazine monomer with the molecular structure shown in formula (1) is cured by heating to obtain: Wherein, A1 and A2 are each independently selected from one of formula (II) to formula (IV), and A1 and A2 may be the same or different; Wherein, R1, R2, and R3 are each independently selected from any one of an aliphatic group, an alicyclic group, or an aromatic group.
2. The bio-based degradable high temperature resistant benzoxazine resin according to claim 1, characterized in that: The aliphatic group is one of methyl, ethyl or n-hexyl; the alicyclic group is 2-furanyl or cyclohexyl; the aromatic group is one of phenyl, p-tolyl, m-tolyl or m-phenylethynyl.
3. A method for preparing a bio-based degradable high temperature resistant benzoxazine resin as claimed in claim 1 or 2, characterized in that: The following steps are involved: S1, adding the primary amine compound and the aldehyde compound A to an organic solvent, stirring and reacting at a temperature of 90 to 120° C. for 10 to 60 minutes to generate a triazine compound; the organic solvent is selected from one or more of ethanol, tetrahydrofuran, acetone, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, dioxane, chloroform, toluene or xylene; S2, adding a bisphenol compound containing a hydroxymethyl diacetal structure and an aldehyde compound B to the solution obtained in step S1, and stirring the reaction at 60-90° C. for 1-15 hours; the bisphenol compound containing a hydroxymethyl diacetal structure is selected from xylitol di-p-hydroxybenzaldehyde acetal or xylitol di-m-hydroxybenzaldehyde acetal; S3, after the reaction is completed, the reaction product is separated, purified, and dried to obtain a benzoxazine monomer; S4, curing the benzoxazine monomer by heating to obtain a benzoxazine resin.
4. The method for preparing the bio-based degradable high temperature resistant benzoxazine resin according to claim 3, characterized in that: The xylitol bis-p-hydroxybenzaldehyde or xylitol bis-m-hydroxybenzaldehyde is prepared by the following method: Take xylitol, p-hydroxybenzaldehyde or m-hydroxybenzaldehyde as reactants, p-toluenesulfonic acid as a catalyst, N,N-dimethylformamide and petroleum ether as solvents, mix them evenly at room temperature, then heat to 80-140° C., stir and react for 8-24 hours, and remove the solvent by rotary evaporation to obtain sugar alcohol bis-p-hydroxybenzaldehyde or xylitol bis-m-hydroxybenzaldehyde.
5. The method for preparing the bio-based degradable high temperature resistant benzoxazine resin according to claim 4, characterized in that: The mass ratio of xylitol, p-hydroxybenzaldehyde or m-hydroxybenzaldehyde, p-toluenesulfonic acid, N,N-dimethylformamide and petroleum ether is 1:(1.1-2.2):(0.05-0.15):(3.60-4.80):(2.40-3.60).
6. The method for preparing the bio-based degradable high temperature resistant benzoxazine resin according to claim 3, characterized in that: The primary amine compound is selected from any one of methylamine, ethylamine, n-hexylamine, 2-furylamine, cyclohexylamine, aniline, p-toluidine, m-toluidine or m-aminophenylacetylene.
7. The method for preparing the bio-based degradable high temperature resistant benzoxazine resin according to claim 3, characterized in that: The aldehyde compounds A and B are both 37% formaldehyde aqueous solution or paraformaldehyde.
8. The method for preparing the bio-based degradable high temperature resistant benzoxazine resin according to claim 3, characterized in that: In step S1, the molar ratio of the amino group of the primary amine compound to the aldehyde group of the aldehyde compound A is 1:(1.0-1.3).
9. The method for preparing the bio-based degradable high temperature resistant benzoxazine resin according to claim 3, characterized in that: In step S2, the molar ratio of triazine, phenolic hydroxyl and aldehyde groups in the three reaction raw materials is 1:(1.3-1.7):(3.0-3.5).
10. A method for degrading the bio-based degradable high temperature resistant benzoxazine resin as claimed in claim 1 or 2, characterized in that: The benzoxazine resin is immersed in a mixed solution for 1 to 48 hours to achieve the purpose of degradation; the mixed solution includes an acid compound and a polar solvent; the acid compound is one or more of an organic acid or an inorganic acid; the polar solvent is one or more of an alcohol compound, a ketone compound, an ether compound or an amide compound.
Citation Information
Patent Citations
Benzoxazine resin with spirocyclic acetal structure and preparation method thereof
CN110551140A
Bio-based degradable benzoxazine resin, and preparation method, cured resin, compound and degradation method thereof
CN112442158A
Main chain type benzoxazine resin, preparation method thereof, bisphthalonitrile-based composite material containing main chain type benzoxazine resin, and composite cured resin containing main chain type benzoxazine resin
CN115403724A
Benzoxazine resin with erythritol acetal structure
CN115433333A
Malleable and degradable benzoxazines
US20230084211A1
Cited By
Degradable armed acetal epoxy monomer and preparation method thereof
CN119613427A